Training communication abilities in Rett Syndrome through reading and writing - FABIO, ROSA ANGELA; CASTELLI, ILARIA; MARCHETTI, ANTONELLA; Antonietti, Alessandro (Frontiers in Psychology, 2013)
The goal of this clinical case study is to investigate the possibility of training communication abilities in people with Rett syndrome (RS). Usually, girls with RS never exceed the sensorimotor stage of development, but the inter-individual variability typical of RS may lead us to doubt the irrevocability of that developmental limit, especially for those girls who are engaged in cognitive rehabilitation. The case study reported here concerns a 21 year old girl with RS who was engaged in cognitive rehabilitation training based upon the principles of Feuerstein’s modificability and mediated learning theory. The training aimed to teach her basic concepts and enhance reading-writing abilities. Statistical analyses showed that the girl reached adequate reading-writing abilities, proving the validity of the cognitive intervention which allowed her to communicate by composing words with her forefinger on an alphabetic table. Although these results need to be cautiously considered as they derive from a single case study, they have implications for future cognitive rehabilitation for deeply impaired clinical conditions as in the case of RS.